Error Correction in Vergence Eye Movements: Evidence Supporting Hering’s Law - John L. Semmlow; Tara L. Alvarez; Bérangère Granger-Donetti (Journal of Eye Movement Research)
In pure symmetrical vergence eye movements, a fusion initiating component quickly brings the eyes close to the desired position. A small error usually remains after this response which must be corrected to attain the small final vergence error (i.e., fixation disparity). Error correction will usually involve both version and version movements so possible mechanisms include: small saccades, smooth pursuit, symmetrical vergence, or some combination. Alternatively, an asymmetrical vergence or uniocular slow eye movement could be used to achieve the highly precise final position. Saccade-free late fusion sustaining components during the steady state to a symmetrical vergence step stimulus are analyzed using independent component analysis. Results suggest that fine correction is most likely the product of closely coordinated version and vergence components.